Mission and Care for the Poor in Sydney Anglican Perspective - Williams, David A. (Mission studies, 2020)
Sydney Anglican theology has a number of distinctive motifs, including its ecclesiology and theology of the gospel. These motifs inform a theology of mission as proclamation that stands in a tradition that places a priority on evangelism. Where does such a missiological construction locate a theology of care for the poor? Answers to this question were explored through semi-structured interviews with faculty at Moore Theological College. The significance of caring for the poor is affirmed. Care for the poor is located in the life of the disciple of Jesus Christ and in the community life of the local church. The implications of this theological view for an understanding of the missio Dei are explored.